2017
DOI: 10.15282/ijame.14.3.2017.5.0352
|View full text |Cite
|
Sign up to set email alerts
|

Empirical modelling of machining parameters for turning operations using multiobjective Taguchi method

Abstract: This paper presents an effective approach for the optimisation of process parameters in the turning operation for machining ASTM A36 Mild Steel bar with multi-performance characteristics using multi-objective Taguchi method. Based on Taguchi orthogonal array, 27 experimental runs were performed to identify the optimal level of process parameters. The multiple performance characteristics including power consumption, surface roughness and frequency of tool vibration were the quality variables considered for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Of course, there is a lot of research that characterises the multi-tool machining and technological capabilities of CNC multi-purpose machines [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The specific issues addressed in these studies ultimately do not provide the theoretical basis for the application and design of multi-tool adjustments.…”
Section: Analysis Of Modern Multi-purpose Cnc Machines For Multi-toolmentioning
confidence: 99%
“…Of course, there is a lot of research that characterises the multi-tool machining and technological capabilities of CNC multi-purpose machines [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The specific issues addressed in these studies ultimately do not provide the theoretical basis for the application and design of multi-tool adjustments.…”
Section: Analysis Of Modern Multi-purpose Cnc Machines For Multi-toolmentioning
confidence: 99%
“…The cutting forces vary to a significant extent depending upon the physical and mechanical properties of the material [11]. The force components were measured and analysed.…”
Section: Machining Forcesmentioning
confidence: 99%
“…It is accredited from the principle of metal cutting that an inspection of machined chip shapes delivers a reasonable way of analysing the cutting physiognomies of a material [11]. The shape of the chip formed in machining is the most important parameter influencing the efficiency of production in the cutting industry.…”
Section: Chip Morphologymentioning
confidence: 99%
“…The feed rate in turning process has a significant effect on surface roughness and power consumption. At higher feed rates the surface roughens increases affecting the quality of the components [18,19]. Authors have not found much work related to roller burnishing effect on surface roughness and microhardness in different conditions.…”
Section: Introductionmentioning
confidence: 99%